HLA-DRB1*16: 01-DQB1*05. Issue 5 (May 2016) - Nicoletti, Paola; Werk, Anneke N.; Sawle, Ashley; Shen, Yufeng; Urban, Thomas J.; Coulthard, Sally A.; Bjornsson, Einar S.; Cascorbi, Ingolf; Floratos, Aris; Stammschulte, Thomas; Gundert-Remy, Ursula; Nelson, Matthew R.; et al.
Abstract : Objective: Flupirtine is a nonopioid analgesic with regulatory approval in a number of European countries. Because of the risk of serious liver injury, its use is now limited to short-term pain management. We aimed to identify genetic risk factors for flupirtine-related drug-induced liver injury (DILI) as these are unknown. Materials and methods: Six flupirtine-related DILI patients from Germany were included in a genome-wide association study (GWAS) involving a further 614 European cases of DILI because of other drugs and 10 588 population controls. DILI was diagnosed by causality assessment and expert review. Human leucocyte antigen (HLA) and single nucleotide polymorphism genotypes were imputed from the GWAS data, with direct HLA typing performed on selected cases to validate HLA predictions. Four replication cases that were unavailable for the GWAS were genotyped by direct HLA typing, yielding an overall total of 10 flupirtine DILI cases. Results: In the six flupirtine DILI cases included in the GWAS, we found a significant enrichment of the DRB1*16:01-DQB1*05:02 haplotype compared with the controls (minor allele frequency cases 0.25 and minor allele frequency controls 0.013; P =1.4×10 –5 ). We estimated an odds ratio for haplotype carriers of 18.7 (95% confidence interval 2.5–140.5, P =0.002) using population-specific HLA control data. The result was replicated in four additional cases, also with a haplotype frequency of 0.25. In the combined cohort (six GWAS plus four replication cases), the haplotype was also significant (odds ratio 18.7, 95% confidence interval 4.31–81.42, P =6.7×10 –5 ). Conclusion: We identified a novel HLA class II association for DILI, confirming the important contribution of HLA genotype towards the risk of DILI generally. Abstract : Supplemental Digital Content is available in the text.